DESAIN INSTRUMEN TES THREE TIERS MULTIPLE CHOICE UNTUK ANALISIS MISKONSEPSI SISWA TERKAIT LARUTAN PENYANGGA (Jurnal Inovasi Pendidikan Kimia, 2019)
The purpose of this study is to find out the feasibility of three tiers test instrument design for analysing students' misconceptions of buffer solutions. The method used was Research and Development (RD) with 4D model, but only till the development stage. Analytical technique done is validity test of 3TMC tes instrument with expert judgment assessment, reliability test using cronbach's alpha formula, and teacher response analysis. The results of expert validation on 3TMC test product received a positive response with a score of 82 and 90 of the total score of 105, so the 3TMC test product was feasible and can be used with a little bit revision. 3TMC product reliability test obtained reliability number of 0.439 with a critical number of 0.335, so the 3TMC test product was reliable. Based on the results of this study it can be concluded that the 3TMC test product was feasible to be used as a test instrument for the analysis of student misconceptions of the buffer solution